Water sorption, water solubility, degree of conversion, elastic indentation modulus, edge chipping resistance and flexural strength of 3D-printed denture base resins. (January 2023) - Greil, Veronika; Mayinger, Felicitas; Reymus, Marcel; Stawarczyk, Bogna
Abstract: Objectives: To investigate the water sorption ( w sp ), water solubility ( w sl ), degree of conversion ( DC), elastic indentation modulus (E IT ), edge chipping resistance ( ECR ) and flexural strength ( FS) of 3D-printed, milled and conventionally polymerized denture base resin materials. Methods: Specimens (N = 540) were 3D-printed (NextDent Denture 3D+ (DEN), Fotodent Denture (FOT), Freeprint Denture (FRE), V-Print dentbase (VPR)), cut (Ivotion Base (IVO)) and molded (PalaXpress (PAL)) in three geometries. W sp, w sl, DC, E IT, ECR and FS were tested initially (24 h, 37 °C, H20) and after additional aging (5000 thermal cycles, 5/55 °C) . Data were analyzed with Kolmogorov-Smirnov, univariate ANOVA, Kruskal-Wallis, Mann-Whitney U test and Spearman's correlation (p < 0.05) Results: Most 3D-printed denture base resins showed higher w sp (25.31–37.94 μg/mm 3 ) and w sl (0.08–8.27 μg/mm 3 ), but also higher E IT (3.11–4.09 GPa) and FS (60.81–99.57N/mm 2 ) values than the control groups. DEN and VPR showed high DC (89.36–93.53%), E IT (3.77–4.09 GPa) and FS (79.65–99.57N/mm 2 ), while FOT showed low w sp (25.31–27.35 μg/mm 3 ) and w sl (1.01–3.87 μg/mm 3 ) values. In all materials, the examined parameters were affected by aging. Significance: Although 3D-printed denture base resins showed promising results with regard to the observed DC and FS, only FOT and FRE surpassed the threshold values defined by the ISO norms. Graphical abstract: Image 1 Highlights: Most 3D-printed denture base resins showed higher w sp and w sl than the control groups. Most 3D-printed resins presented higher E IT and FS values than the control groups. In all materials, the examined parameters were affected by aging. Only one 3D-printed material met the standards set by the ISO norm.